1988
DOI: 10.1523/jneurosci.08-02-00472.1988
|View full text |Cite
|
Sign up to set email alerts
|

Glycine and glycine receptor immunoreactivity in brain and spinal cord

Abstract: To study the distribution of glycine immunoreactive neurons in the spinal cord and brain, antisera were raised against glycine conjugated to protein carriers. High-titer rabbit glycine antiserum was purified by affinity chromatography. Testing against other amino acids and peptides with immuno dot blots and ELISA assays showed little apparent cross-reaction with glutamate, aspartate, glutamine, taurine, and 17 other amino acids and related compounds. Similarly, the antiserum showed little apparent recognition … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
101
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(115 citation statements)
references
References 26 publications
12
101
1
Order By: Relevance
“…Most glycine-LI synapses were symmetrical, but in a few instances asymmetrical synapses were found, which was in agreement with the situation in the rat [21]. In the dorsal horn, however, Todd [18] reported only the symmetrical type.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Most glycine-LI synapses were symmetrical, but in a few instances asymmetrical synapses were found, which was in agreement with the situation in the rat [21]. In the dorsal horn, however, Todd [18] reported only the symmetrical type.…”
Section: Discussionsupporting
confidence: 82%
“…In the dorsal horn, however, Todd [18] reported only the symmetrical type. The synaptic vesicle shape in glycine-LI presynaptic boutons was of the pleomorphic or elongated type, as reported previously [14,16,21]. As for the correlation between vesicle shape and the function of the chemical synapse, it has been suggested that axon terminals containing round vesicles are excitatory and those containing elongated vesicles are inhibitory [20].…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…High concentrations of neurotransmitter such as GABA and glycine are also present in a sub-population of mature WM axons in several species (Carlton et al, 1996;Davanger et al, 1991;Rogers and Pow, 1995;Todd and Sullivan, 1990;van den Pol and Gorcs, 1988;Wilson et al, 1996). Block of GABA uptake mimics the effects of GABA upon axon conduction in the neonatal rat optic nerve (Sakatani et al, 1991), while block of catecholamine uptake mimics the effect of nor-adrenaline (Nikolaeva et al, 2009); observations consistent with tonic operation of functional neurotransmitter uptake in the tissue.…”
Section: Gaba and Glycinementioning
confidence: 62%